Deviation from prescribed drug treatment after discharge from hospital. Issue 6037 (18th September 1976) - Parkin, D M; Henney, C R; Quirk, J; Crooks, J
Abstract : A study of 130 patients discharged from four hospital wards dealing mainly with acute medical cases showed that 66 deviated from the drug regimen prescribed on discharge. Of the patients, 46 did not have a clear understanding of the regimen (non-comprehension) and 20 of the remaining 84 patients understood the prescribed regimen but did not follow the instructions (non-compliance). The prescribing of complex drug regimens, and the availability of medicines prescribed before admission to hospital appeared to be the two main factors influencing non-comprehension and non-compliance.